Application of a Validated Stability-Indicating LC Method for the Simultaneous Estimation of Tapentadol and Its Process-Related Impurities in Bulk and Its Dosage Form - Singaram Kathirvel; Suggala Venkata Satyanarayana; Garikapati Devalarao (Journal of Chemistry)
Described is a first reported, simple, rapid, selective, and isocratic stability-indicating RP-LC method for the quantitative determination of tapentadol and its related substances in bulk samples and pharmaceutical dosage forms in the presence of its two process-related impurities. Chromatographic separation was achieved on the reversed phase, Enable column (C18 (5-μm, 250 × 4.6 mm, i.d.)) at ambient temperature using a mobile phase consisting of 0.02 M potassium dihydrogen orthophosphate (adjusted to pH 6 with 1 M KOH) and acetonitrile (80 : 20, v/v). Flow rate was 1 mL/min and retention time was found to be 7.7 ± 0.05 min. Quantitation was achieved with UV detection at 215 nm based on peak area with linear calibration curves at concentration range 75–300 μg/mL. Forced degradation studies were performed, in accordance with ICH guidelines, using acidic, alkaline, oxidative, neutral, photolytic, and thermal conditions. The drug was found to be stable under all the conditions. The developed method was validated in terms of precision, robustness, recovery, and limits of detection and quantitation. Regression analysis shows an “r” value (correlation coefficient) of greater than 0.999 for tapentadol and two potential impurities.